Perlindungan Anak Berbasis Masyarakat Perspektif Fiqh Siyasah Tanfidziyah - Syafira Dini Asmarani (Jurnal Ilmiah Kutei, 2025)
Child protection refers to all efforts made to create conditions in which every child can fulfill their rights and responsibilities for their proper physical, mental, and social development and growth. The state must take action to prevent and address acts of violence against children, as such acts constitute a violation of human rights. This study analyzes the implementation of Article 12 of Regent Regulation Number 30 of 2021 concerning Community-Based Child Protection, as well as the perspective of Fiqh Siyasah Tanfīdziyah on the implementation of this policy. The purpose of this study is to examine the implementation of Article 12 of the Regent Regulation of Pringsewu Regency Number 30 of 2021 on Community-Based Child Protection and to review it from the perspective of Fiqh Siyasah Tanfīdziyah. This research employs a qualitative descriptive method with a field study approach conducted at the Office of Women Empowerment, Child Protection, Population Control, and Family Planning of Pringsewu Regency. The findings indicate that the policy implementation is still constrained by cross-sectoral coordination, as evidenced by the absence of regular meetings between relevant agencies and village authorities, as well as overlapping authorities in program execution. Budget limitations are reflected in the lack of supporting facilities in the field, such as the inadequate provision of child protection facilities. Nevertheless, the policy is still considered consistent with the principle of maslahah in child protection and the state’s responsibility as outlined in the perspective of Fiqh Siyasah Tanfīdziyah.